ANIMATION MEDIA FOR MATHEMATICS LEARNING INFORMATION SYSTEMS - David David; Jimmy Pratama (Universitas Internasional Batam, 2022)
In this era of advanced technology, many works have emerged and one of them is Animation. Animation is a series of various images that form a movement that becomes one. Animation has the advantage of showing and explaining circumstances that change over time. Animation is supported to form a mental picture from the drawn and requires regular learning effort. Learn animation to awaken the imagination that is in the brain and make it real that can be seen directly from the results formed. Creating animations for learning purposes is not the same as just for entertainment, but the results obtained require knowledge of information presented with dynamic illustrations processed by the human brain.